Expatriate managers' immersion in another culture: a phenomological study of lived experiences - Russell, Roger Chesley (Curtin University, 2006)
Although adjusting to a foreign culture is not easy, being immersed in another culture is an experience lived by a growing number of persons in the globalized world. For expatriate managers, successful adjustment is imperative and fundamental in establishing overall effectiveness during overseas assignments. It is intriguing that organizations often blame the individual when expatriate assignments fail (Deresky 2002; Hodgetts and Luthans 2000; Swaak 1995a; Tung 1987) rather than recognizing that others may lack understanding of what it is like to be immersed in another culture. A study of Canadian expatriate managers who have worked in non-government organizations (NGOs) in Indonesia is presented. The research focuses on interpreting the lived experience of expatriate managers using their own words and meanings. Written descriptions from research participants were obtained via email and analysed/synthesized using Giorgi's descriptive phenomenological method (Giorgi 1975; 1985; Giorgi & Giorgi 2003). The central finding of the study is that expatriates experience paradoxical ways of being including feelings of: understanding/not understanding, discomfort/comfort, powerfulness/powerlessness, belonging/not belonging, being open to the new culture/yet holding on to own culture, freedom/restriction, being supported/not supported, and being unchanged/changed when immersed, living and working in another culture. The new knowledge and understanding obtained from this research may result in alterations to present human resource management practices and strategies utilized in facilitating and supporting expatriate assignments. These changes will enhance the experience for expatriate managers and organizations alike.